2002
DOI: 10.1002/1522-2675(200211)85:11<3657::aid-hlca3657>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of -Substituted N-Methylsulfonamides

Abstract: Dedicated to Professor Dieter Seebach on the occasion of his 65th birthday A novel amine auxiliary for the asymmetric synthesis of a-substituted N-methylsulfonamides is described. The reaction of 4-([1,1'-biphenyl]-4-yl)-2,2-dimethyl-1,3-dioxan-5-amine (16) with various aliphatic sulfonyl chlorides afforded the corresponding sulfonamides, which were lithiated and subsequently reacted with electrophiles to give the corresponding products in high yields and good-to-excellent asymmetric inductions (de 83 ± 95%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Traditional methods (Figure b) for direct alkylation of sulfonamides require strong bases, reactive electrophiles, low temperatures and the use of stoichiometric amounts of polar additives [such as tetramethylethylenediamine (TMEDA), hexamethylphosphoramide (HMPA), and phenanthroline]; several recent reports have described metal‐catalysed α‐arylation of alkyl sulfonamides (Figure c), but only the methods from Zhou et al (who reported a single example of branched sulfonamide synthesis) and Knauber and Tucker deliver α‐sp 3 ‐substituted benzylsulfonamides as products. Furthermore, to date there have been few disclosures of methods to enable catalytic sp 3 –sp 3 coupling to allow α‐functionalisation of sulfonamides.…”
Section: Figurementioning
confidence: 99%
“…Traditional methods (Figure b) for direct alkylation of sulfonamides require strong bases, reactive electrophiles, low temperatures and the use of stoichiometric amounts of polar additives [such as tetramethylethylenediamine (TMEDA), hexamethylphosphoramide (HMPA), and phenanthroline]; several recent reports have described metal‐catalysed α‐arylation of alkyl sulfonamides (Figure c), but only the methods from Zhou et al (who reported a single example of branched sulfonamide synthesis) and Knauber and Tucker deliver α‐sp 3 ‐substituted benzylsulfonamides as products. Furthermore, to date there have been few disclosures of methods to enable catalytic sp 3 –sp 3 coupling to allow α‐functionalisation of sulfonamides.…”
Section: Figurementioning
confidence: 99%
“…Chromatographic separation of racemates provided initial materials, but on larger scale this method became increasingly impractical. An examination of the literature at that time suggested only two known approaches for asymmetric synthesis (Scheme ): (1) an auxiliary mediated alkylation as exemplified by the method of Enders (eq 1) or (2) the opening of β-sultones and sultams as described by Peters , (eq 2).…”
mentioning
confidence: 99%
“…Enders’ method represents the most diastereoselective alkylation procedure described to date. Unfortunately, the auxiliary itself requires a 10-step synthesis and must ultimately be cleaved by harsh acidic conditions. Even after such vigorous treatment, a methyl substituent remains on the sulfonamide nitrogen, limiting the scope of accessible products and making it unsuitable to our needs.…”
mentioning
confidence: 99%